2014
DOI: 10.1002/chem.201302455
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Extended Open Frameworks with Fluorescent Tags for Sensing Explosives: Competition between Size Selectivity and Electron Deficiency

Abstract: Three new electron-rich metal-organic frameworks (MOF-1-MOF-3) have been synthesized by employing ligands bearing aromatic tags. The key role of the chosen aromatic tags is to enhance the p-electron density of the luminescent MOFs. Single-crystal X-ray structures have revealed that these MOFs form three-dimensional porous networks with the aromatic tags projecting inwardly into the pores. These highly luminescent electron-rich MOFs have been successfully utilized for the detection of explosive nitroaromatic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(134 citation statements)
references
References 108 publications
2
130
2
Order By: Relevance
“…Similar with common luminescent materials, the luminescence of MOFs can be influenced by many environmental factors,3, 4 including physical stimulus and chemical stimulus (ions,30, 31, 32, 33 solvents,34, 35, 36 vapors,37 pH,38, 39 gases,1 and so on40, 41, 42, 43, 44, 45). However, unlike other luminescent materials, the intrinsic porosity, large surface area, and strong adsorption affinity of MOFs can effectively enrich guest species.…”
Section: Introductionmentioning
confidence: 99%
“…Similar with common luminescent materials, the luminescence of MOFs can be influenced by many environmental factors,3, 4 including physical stimulus and chemical stimulus (ions,30, 31, 32, 33 solvents,34, 35, 36 vapors,37 pH,38, 39 gases,1 and so on40, 41, 42, 43, 44, 45). However, unlike other luminescent materials, the intrinsic porosity, large surface area, and strong adsorption affinity of MOFs can effectively enrich guest species.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering work within this field was performed by Li et al who demonstrated the sensitive detection of DMNB and 2,4-DNT in the vapour phase. 37 This work inspired a number of other researchers who subsequently demonstrated the successful detection of explosives, with some selectivity, using zinc, [38][39][40][41][42][43] cadmium, [44][45][46] lithium, 47 indium, 48 europium, [49][50][51][52] and terbium containing metal-organic frameworks. 53 However, the majority of the published research reports the detection of explosives using MOFs through solution-based titrations.…”
Section: −3mentioning
confidence: 89%
“…In this regards, supramolecular polymers and metal-organic frameworks (MOFs) have emerged as highly promising materials in recent times for sensing NACs explo- TNT high [34] sives. [35][36][37] Our designed discrete systems are quite selective for electron poor nitroaromatics. After achieving such selectivity, the next objective would be to enhance sensitivity so that the presence of even a few molecules of explosive can be detected efficiently.…”
Section: Discussionmentioning
confidence: 99%